Pembatasan Jarak Presensi Dalam Sistem Presensi Daring Menggunakan Formula Haversine - Ilham, Baga Pardana; Supriadi, Fidi (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2024)
The transformation of the manual attendance system into an online system has been carried out by various parties, including government agencies, offices, and schools. For example, a school that has implemented an electronic-based learning management system can use the attendance form feature as a way to record students' attendance in the learning process. However, this feature is considered to have shortcomings when applied during face-to-face learning in class because absent students can still fill in from wherever they are as long as they can access the form. The existence of a radius limit is necessary to limit only students who are within the range of the class area to be able to fill out the attendance form. This research aims to design an online presence system by applying the haversine formula using the Extreme Programming method. This formula was chosen because it is suitable for calculating the distance between two coordinate points on the earth's surface assuming the earth is round. Extreme Programming is a method for building fast software systems that consists of planning, design, coding, and testing phases. Through 30 experiments, a percentage of 96.6% was obtained, which shows that the haversine formula can be applied to limit the distance in a presence system.